The ALH online review (Oxford University Press, 2015)
"The ALH Online Review is a source for in-depth reviews assessing the significance of new books for specialists in American literary history. The Review engages scholarly and critical studies by deliberating on important shifts and advances in various sub-fields, and exploring major developments in research."
Gesehen am 02.12.2025
Keywords: Zeitschrift